Effects of the Decompression Treatment Model on Delinquent Behavior in Youth with Elevated Psychopathic Traits: A Systematic Review - Dovijanić, Sofija Đ.; Maljković, Marija N. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
Psychopathic traits correlate with a disregard for social norms, frequent rule-breaking, and early-onset delinquency. Such youth present particular challenges in institutional treatment due to their uncooperative and disruptive behavior. Nevertheless, empirical findings suggest that specialized interventions, such as the Decompression Treatment Model (DTM), may be effective in reducing delinquent behavior. DTM is a high-intensity, long-term cognitive-behavioral intervention designed to reduce aggression, enhance interpersonal functioning, and support social reintegration. The main goal of this systematic review was to examine and qualitatively synthesize evidence on the effects of DTM. Following PRISMA 2020 guidelines, eight empirical studies were identified and analyzed. Findings across these studies indicate that full participation in program activities is associated with a moderate, long-term reduction in violent and nonviolent recidivism, as well as a substantial decrease in uncooperativeness during treatment exposure. Overall, the evidence suggests that even the most serious forms of antisocial behavior among young offenders can be modified, particularly among those with violent tendencies and pronounced interpersonal features of psychopathy such as superficial charm and narcissism.
Keywords: decompression treatment model; psychopathy; juvenile offender; institutional treatment; systematic review